Obstacles and Positive Outcomes from Teacher Professional Development (TPD) Program Implementation in Yogyakarta: English Teachers’ Experience - Santa Monica (Journal of English Language Teaching and English Linguistics, 2023)
Research focused on Teacher Professional Development (TPD) programs is abundant worldwide, aiming to enhance teachers' growth, skills, awareness, and, most importantly, improve the teaching-learning process both within and outside classrooms. However, such studies are notably lacking in the Indonesian context. Therefore, this study addresses the following research questions: 1. What do English teachers perceive as the benefits of TPD programs? 2. What are the main challenges encountered by English teachers in TPD? To address these inquiries, this research employs both quantitative and qualitative methods to gather necessary data. A total of 73 senior high school English teachers in Yogyakarta city and Sleman regency participated in the survey through questionnaires, followed by in-depth interviews with five participants. The findings reveal two prominent challenges faced by the participants: managing workload and time effectively and the absence of a follow-up program. By identifying these challenges, this study also offers recommendations for changes and enhancements to TPD programs in Indonesia, as inferred from the study's implications.